2017
DOI: 10.1016/j.bpj.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Slow Spontaneous Release of 11-cis-Retinal from Rhodopsin

Abstract: The vertebrate visual photoreceptor rhodopsin (Rho) is a unique G protein-coupled receptor as it utilizes a covalently tethered inverse agonist (11-cis-retinal) as the native ligand. Previously, electrophysiological studies showed that ligand binding of 11-cis-retinal in dark-adapted Rho was essentially irreversible with a half-life estimated to be 420 years, until after thermal isomerization to all-trans-retinal, which then slowly dissociates. This long lifetime of 11-cis-retinal binding was considered to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…Incidentally, incubating unbleached, dark-adapted mouse rods with 11-cis-retinal did not have any obvious effect on dark noise (SI Appendix,Fig. S2), confirming previous reports of relatively negligible Opn in the absence of bleaching(28)(29)(30)(31).…”
supporting
confidence: 87%
“…Incidentally, incubating unbleached, dark-adapted mouse rods with 11-cis-retinal did not have any obvious effect on dark noise (SI Appendix,Fig. S2), confirming previous reports of relatively negligible Opn in the absence of bleaching(28)(29)(30)(31).…”
supporting
confidence: 87%
“…Bicelles are model membranes that consist of long-chain phospholipids, which form the planar lipid bilayer segment, and detergents or short-chain phospholipids, which stabilize the edge of the bilayer. In an earlier report (12), we showed that dark-state Rho was stable in 1% (w/v) POPC/CHAPS bicelles over the timescale of weeks. Here, we evaluated the stability of opsin in POPC/CHAPS bicelles (Fig.…”
Section: Popc/chaps Bicelles Improve the Thermal Stability Of Photoblmentioning
confidence: 74%
“…The first assay based on the intrinsic tryptophan (Trp) fluorescence of Rho has been described in Tian et al (12) and Farrens and Khorana (13). In brief, Trp fluorescence can be quenched by 11CR in the dark-state Rho (Fig.…”
Section: Fret-based Assays To Measure the Kinetics Of 11cr Binding Tomentioning
confidence: 99%
See 2 more Smart Citations